γ-aminobutyric acid (GABA) accumulations in rice during germination - Panatda Jannoey (2018)
GABA (γ-Aminobutyric acid)-enriched rice becomes a popular healthy food nowadays. It has a major inhibitory neurotransmitter function. It inhibits cancer cell proliferation and also reduces blood pressure. GABA concentrations in rice grains and leaves of five well-known rice cultivars were investigated during germination. After germination of whole rice grains, hull and young leaves were removed and grains was used for consumption. Young leaves, waste from rice milling process, and germinated rice grains were collected to determine GABA concentrations by LC-MS after 2-hydroxynaphthaldehyde (HN) derivative formation. Although all of the cultivars have different initial glutamic acid concentrations, GABA concentrations in rice were not different among them (p>0.05). The GABA concentrations in rice grains and leaves were dramatically increased with germination days. However, rice leaves contained more GABA than rice grains by 2-3 folds in all rice cultivars. The highest GABA concentrations in rice grains and young leaves were found at 20 and 30 germination days, respectively. After 20 days of germination, GABA concentrations in rice grains were decreased. GABA concentrations in germinated rice grains were found to be 0.19-1.25 mg/g in Pitsanulok2 (PL2) rice; 0.30-2.01 mg/g in Chainat1 (CN1) rice; 0.51-2.45 mg/g in Kawdokmali 105 (KDML 105) rice; 0.34-1.74 mg/g in Supan 1 (SP1) rice and 0.39-1.59 mg/g in Patum1 (PT1) rice cultivars during germination. In contrast, rice leaves showed increased GABA concentrations until 30 germination days. The GABA concentrations were shown to be 1.45-3.14 mg/g, 1.36-2.85 mg/g, 2.39-2.52 mg/g, 0.82-2.09 mg/g and 1.33-1.50 mg/g in normal rice PL2, CN1, KDML 105, SP1 and PT1, respectively. Data of the GABA accumulation and disappearance in rice produced by germination method were presented. These results support effective uses of germinated rice grains for consumption and rice leaves for pharmaceutical application.